Landscape and meteorological determinants of malaria vectors’ presence and abundance in the rural health district of Korhogo, Côte d’Ivoire, 2016- 2018, and comparison with the less anthropized area of Diébougou, Burkina Faso - Jaime, Glória; Hobeika, Alexandre; Figuié, Muriel (My University, 2020)
Background: The significant increase in antibiotics resistance (AMR) has become a major issue over the last decade. Current international focus falls largely on reducing the excessive use and misuse of antibiotics in animal farming. The drivers of this consumption are generally studied through farmers' behavior and veterinary-farmers interactions. However, drug use also results from structural factors that determine the functioning of the drugs market chain and farmers' access to drugs. This article presents an overview of the limits to access to veterinary drugs in sub-Saharan Africa (SSA), as well as the international policy tools and setups that claim to improve it. Method: We analyze the scientific and grey literature, the publicly available data of the veterinary pharmaceutical industry and international organizations in order to gather information on the veterinary drugs markets in SSA, and on the norms, recommendations, guidelines and initiatives at international level that impact the functioning of the markets chains in SSA. Findings: We highlight numerous roadblocks to access to veterinary medicines in SSA. The African market is highly dependent on imports. It suffers from a high level of fragmentation, weak distribution infrastructures and services and is driven by the multiplication of private non- professional actors playing a growing role in the veterinary drug chains. The distribution system is increasingly dualized, with on the one hand the public sector (supported by development organizations) supplying small scale farmers in rural areas, but with limited and irregular means; and on the other side a private sector largely unregulated which supplies commercial and industrial farming systems. Different innovations have been developed at the international level to lower these barriers, such as homogenization of national legislations, donations and vaccine banks. Along decades-old inter-state cooperation, many new forms of Public-Private partnerships and hybrid forums are emerging, signaling a growing power of the private sector in the global governance. Conclusions: In sub-Saharan Africa (SSA), access to veterinary drugs is far from a given and remains an issue for many farmers. Drugs access is highly heterogeneous, little regulated and the market chains are increasingly segmented. The duality of the structure of the market chains has significant implications for the strategies aiming at controlling AMR at global level. Many of them emphasize the need to reduce the use of antibiotics at farm levels, without embracing this duality within countries. These strategies need to take to take into account the diversity of the conditions of access and use of drugs. Policies aimed at regulating the risks associated with the use of some drugs, especially antimicrobials, should not only focus on end users, farmers and veterinarians, but also encompass the actors that influence the flow of these compounds.
Keywords: access to medication; market chain; regulation; sub-Saharan Africa; veterinary medicine